2012
DOI: 10.1182/blood-2011-09-379453
|View full text |Cite
|
Sign up to set email alerts
|

F8 gene mutation type and inhibitor development in patients with severe hemophilia A: systematic review and meta-analysis

Abstract: This systematic review was designed to provide more precise effect estimates of inhibitor development for the various types of F8 gene mutations in patients with severe hemophilia A. The primary outcome was inhibitor development and the secondary outcome was high-titerinhibitor development. A systematic literature search was performed to include cohort studies published in peer-reviewed journals with data on inhibitor incidences in the various F8 gene mutation types and a mutation detection rate of at least 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
312
1
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 312 publications
(337 citation statements)
references
References 61 publications
19
312
1
5
Order By: Relevance
“…We first investigated the association of the different severe hemophilia-causing mutations with inhibitor-development in our cohort ( Table 1). As previously reported, 29,30 missense mutations were associated with a significantly lower risk of inhibitor formation (OR 0.46, 95% CI 0.22-0.9, P=0.02).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…We first investigated the association of the different severe hemophilia-causing mutations with inhibitor-development in our cohort ( Table 1). As previously reported, 29,30 missense mutations were associated with a significantly lower risk of inhibitor formation (OR 0.46, 95% CI 0.22-0.9, P=0.02).…”
Section: Resultssupporting
confidence: 65%
“…In the logistic regression analysis, patients with inversions in intron 1 or intron 22 were pooled in the same group to reach a sufficient number of cases. 29 Statistical significance was accepted at P<0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 50% of severe hemophilia A (FVIII ,1%) has been attributed to large DNA inversions mediated through sequences in F8 intron 22 (;45%) or F8 intron 1 (2% to 5%) and homologous sequences distal to the F8 gene, which result in disruption of the F8 gene. 7,18,19 To detect these common F8 inversions, MIPs were designed to capture ligated mutant or reference sequences using an approach similar to the inverse-shifting polymerase chain reaction (PCR) methodology described by Rossetti et al 20 Briefly, 500 ng of genomic DNA was cleaved by Ksp22I (SibEnzyme US LLC, West Roxbury, MA) (1 hour at 37°C), followed by heat inactivation (20 minutes at 65°C), and subsequently ligated with T4 Ligase (New England Biolabs Inc., Ipswich, MA) (16 hours at 15°C) followed by heat inactivation (10 minutes at 65°C). The Ksp221 digested/ ligated product (25 ng) was combined with 100 ng of unmodified genomic DNA prior to PCR amplification and MIP capture (Figure 1).…”
Section: F8 and F9 Gene Variant Analysismentioning
confidence: 99%
“…[1][2][3][4][5] Determination of the causative genetic variant in families affected by hemophilia is important for use in reproductive planning, for use in pregnancy and neonatal management, and also to inform risks of neutralizing antibody (inhibitor) formation and bleeding severity. [6][7][8][9][10][11][12] Therapies targeted to specific mutations have been studied and are likely to become more common in the future. 13 In 2012, 2 separate surveys, 1 distributed to hemophilia providers through the American Thrombosis Hemostasis Network (ATHN) and the other distributed to the patient community through the National Hemophilia Foundation, found that only ;20% of the hemophilia patients in the United States had had their genotype determined.…”
Section: Introductionmentioning
confidence: 99%
“…Both genetic and non-genetic risk factors for inhibitor formation have been identified. [2][3][4] Genetic risk factors include F8 gene mutation 5 and poly-morphisms in IL10, TNFA, FCGR2A and CTLA4. 6,7 Moreover, large epidemiological studies have shown that treatment intensity of hemophilia A patients is also linked to inhibitor development.…”
Section: Introductionmentioning
confidence: 99%